Global food production under alternative scenarios - Huan-Niemi, Ellen; Niemi, Jyrki; Niemi, Janne (us, 2010)
The aim of this study is to project global food production until 2030 under four scenarios: prolonged world economic recession, climate change mitigation policies, complete removal of only EU agricultural subsidies, and total trade liberalisation for agriculture worldwide. The simulations demonstrate that large and highly populated countries like China and India have the potential to be large net exporter of meat products. India is projected to be a major bovine meat exporter, and China is projected to be the main poultry and pigmeat exporter under trade liberalisation. Nevertheless, the ability of these countries to increase meat production at such a rapid rate and conquer the export market can be debated due to the numerous constraints face by these countries.
Keywords: Ma; maatalouskauppa; vapautuminen; EU; maataloustuet; talouskriisit; ilmastosopimukset; maataloustuotanto; Euroopan Unioni; tukimuodot; global food production; agricultural trade liberalisation; climate policy; EU; economic recession